Longitudinal field controls vector vortex beams in anisotropic epsilon-near-zero metamaterials - Vittorio Aita; Diane J. Roth; Anastasiia Zaleska; Alexey V. Krasavin; Luke H. Nicholls; Mykyta Shevchenko; Francisco J. Rodríguez-Fortuño; Anatoly V. Zayats (Nature Communications)
Abstract Structured light plays an important role in metrology, optical trapping and manipulation, communications, quantum technologies and nonlinear optics. Here, we demonstrate an alternative approach for the manipulation of vector beams carrying longitudinal field components using metamaterials with extreme anisotropy. Implementing vectorial spectroscopy, we show that the propagation of complex beams with inhomogeneous polarization is strongly affected by the interplay of the metamaterial anisotropy with the transverse and longitudinal field structure of the beam. This phenomenon is especially pronounced in the epsilon-near-zero regime, exclusively realised for light polarized along the metamaterial optical axis, strongly influencing the interaction of longitudinal fields with the metamaterial. The requirements on the balance between the transverse and longitudinal fields to maintain a polarization singularity at the beam axis allow control of the beam modal content, filtering diffraction effects and tailoring spatial polarization distributions. The understanding of the interaction of vector beams with metamaterials opens new opportunities for applications in microscopy, information encoding, biochemical sensing and quantum technologies.